A Pilot Randomized Controlled Trial of Smoking Cessation in an Outpatient Respirology Clinic. Issue 2 (2015) - Pakhale, Smita; Baron, Justine; Armstrong, Michael A; Garde, Avanti; Reid, Robert D; Alvarez, Gonzalo; Aitken, Debbie; Mullen, Kerri-Anne; Wells, George; Pipe, Andrew
Abstract : OBJECTIVE: To assess the feasibility and potential effectiveness of a modified version of the Ottawa Model for Smoking Cessation in an outpatient respirology clinic. METHODS: Adult tobacco smokers attending the respirology clinic and willing to choose a quit date within one month of enrollment were randomly assigned to receive standard care or the intervention. Standard care participants received smoking cessation advice, a brochure and a prescription for smoking cessation medication if requested. Intervention participants received a 110 voucher to purchase smoking cessation pharmacotherapy and were registered to an automated calling system. Answers to automated calls determined which participants required nurse telephone counselling. Feasibility indicators included recruitment and retention rates, and intervention adherence. The effectiveness indicator was self-reported smoking status at 26 to 52 weeks. RESULTS: Forty-nine (54.4%) of 90 eligible smokers were randomly assigned to the intervention (n=23) or control (n=26) group. Self-reported smoking status at 26 to 52 weeks was available for 32 (65.3%) participants. The quit rate for intervention participants was 18.2% compared with 7.7% for controls (OR2.36 [95% CI 0.39 to 14.15]). CONCLUSION: It would be feasible to evaluate this intervention in a larger trial. Alternatives to face-to-face follow-up at the clinic are recommended.